Incidencia e infestación de Hypsipyla grandella aplicando técnicas de control físico y etológico en jardines clonales de Cedrela odorata “Cedro” en Loreto, Perú 2023 - Reátegui Arévalo, Geybel Saisia (2024)
The objective of this research was to determine the degree of incidence and infestation of Hypsipyla grandella by applying physical and ethological control techniques in clonal gardens of Cedrela odorata "cedro" in Loreto, Peru. An experimental study was carried out using four treatment groups: yellow light, white light, cage and a control. 100 cedar plants were used in each treatment and 20 cedar plants in the control (320 cedar plants). Variables such as the presence of larvae, shoot damage and number of larvae per shoot were evaluated. The results showed statistically significant differences in the incidence and infestation of Hypsipyla grandella. The shade house exhibited zero (0) incidence of the pest, while the yellow light and white light groups were 3 to 19% and 3 to 14% respectively compared to the control group which was 20 to 100%. In addition, the shade house provided effective protection against pest damage, whose damage per shoot and number of larvae per shoot was zero (0) and in the yellow light and white light the average was 2.72 and 3.68 considerably low compared to the control group whose average reached 11 larvae per shoot. It is concluded that the physical protection provided by the cage is highly effective in preventing the incidence of Hypsipyla grandella on Cedrela odorata, practically eliminating its occurrence. Although the yellow and white lights do not provide as strong protection as the shade net house, they significantly reduce incidence. In terms of infestation, the cage stands out as the most effective method, virtually eliminating outbreak damage and larval infestation.